"I bring them here to tell their stories": Transnational Latina mothers' critical literacy practices in an intergenerational storytelling workshop. Issue 5 (14th February 2023) - Gonzales, Grace Cornell; Machado, Emily; Plitkins, Lauren
Abstract: Family literacy programs are potential spaces of empowerment for transnational families, yet often draw from deficit logics that fail to acknowledge the rich language and literacy practices of Latinx communities. We brought together theories of critical literacy and theories of mothering as critical work to document how transnational Latina mothers in an intergenerational storytelling workshop reshaped the space toward their own goals. We explored how mothers in the workshop served as critical literacy pedagogues by writing, reading, and redesigning the workshop space in ways that asserted agency, fostered intergenerational learning, and pushed back against deficit narratives. We offer insights from the workshop experience to suggest ways in which educators, both in family literacy and K–12 settings, can learn from and partner with transnational parents.